Event-Based Modularization of Reactive Systems - Malakuti, Somayeh; Aksit, Mehmet (Concurrent Objects and Beyond, 2014)
There is a large number of complex software systems that have reactive behavior. As for any other software system, reactive systems are subject to evolution demands. This paper defines a set requirements that must be fulfilled so that reuse of reactive software systems can be increased. Detailed analysis of a set of representative languages reveals that these requirements are not completely fulfilled by the current programming languages and as such reuse of reactive systems remains a challenge. This paper explains Event Composition Model and its implementation the EventReactor language, which fulfill the requirements. By means of an example, the suitability of the EventReactor language in creating reusable reactive systems is illustrated.